Average inflation targeting and the interest rate lower bound - Flora Budianto; Taisuke Nakata; Sebastian Schmidt (European Central Bank (ECB), 2020)
Assigning a discretionary central bank a mandate to stabilize an average in ation rate| rather than a period-by-period in ation rate|increases welfare in a New Keynesian model with an occasionally binding lower bound on nominal interest rates. Under rational expecta- tions, the welfare-maximizing averaging window is infinitely long, which means that optimal average in ation targeting (AIT) is equivalent to price level targeting (PLT). However, AIT with a finite, but sufficiently long, averaging window can attain most of the welfare gain from PLT. Under boundedly-rational expectations, if cognitive limitations are sufficiently strong, the optimal averaging window is finite, and the welfare gain of adopting AIT can be small.
Keywords: E31; E52; E58; E61; E71; 330; Monetary Policy Objectives; Makeup Strategies; Liquidity Trap; Deationary Bias; Expectations